MAGNETOCHRONOLOGY OF THE CLIMATIC OPTIMUM AT THE EARLY-MIDDLE MIOCENE TRANSITION IN NORTHEAST RUSSIA - Shilo N.A.; Minyuk P.S. (My University, 2006)
The Miocene was characterized by sharp climatic fluctuations. Among them, the most significant (for high latitudes) fluctuations are termed climatic optimums I, II, and III. Optimum I, which marks the Early–Middle Miocene transition, has been comprehensively studied within and beyond Northeast Russia. In the Russian literature, Optimum I is known as the “beech” horizon first defined by Kartashova based on palynological data. This horizon, a reliable reference unit for the Miocene, is recognized in almost all regions of Northeast Russia with Lower–Middle Miocene sediments.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен